When two lines are perpendicular, the product of their gradients is -@. Therefore the gradient of the line we need is -⅔. This is the x coefficient, so we have y=-⅔x+a where a is the y intercept.

Plug in the point (4,6): 6=-⅔×4+a, 6+8/3=a and a=26/3. So y=-⅔x+26/3=⅔(13-x).

Get rid of the fraction and we have 3y=2(13-x)=26-2x. In general form this is: 2x+3y-26=0.

- All categories
- Pre-Algebra Answers 12,316
- Algebra 1 Answers 25,283
- Algebra 2 Answers 10,443
- Geometry Answers 5,181
- Trigonometry Answers 2,640
- Calculus Answers 6,012
- Statistics Answers 3,020
- Word Problem Answers 10,111
- Other Math Topics 6,651

81,657 questions

85,896 answers

2,190 comments

69,333 users